DIVERSITY AND ECOLOGY OF SOIL INSECTS (ORTHOPTERA) IN HAZARIBAG SANCTURY, JHARKHAND - SANYAL, P.; SAHA, T. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In the sanctuary insects have great role in the multimit cycling and they play significant role in the niche breadth and niche overlap of bird community. This paper deals with orthopteran insect diversity fluctuation in Hazaribagh sanctuary to certain edaphological factors. Species diversity index, species evenness and species richness has been estimated to see seasonal variations of the insect group.